The Analysis Of ESG Score On Corporate Financial Distress Risk In Emerging And Developed Countries In Asia - Sanamira Aliazahra; Zaäfri Husodo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to examine how Environmental, Social, and Governance (ESG) performance affects the risk of non-financial public corporations in emerging and developed Asian nations over eight years from 2016 to 2023. Refinitiv Eikon data was used to collect data for this study, yielding a result of 208 companies across emerging Asian countries and 143 companies in developed Asian countries. The data were then processed through a regression model, where the dependent variable was the ESG scores and the independent variable was the firm financial distress risk, which was measured by the Altman Z-Score model. The findings of the study prove that improving ESG performance can help reduce firm financial distress risk for emerging Asian countries in the non-manufacturing sector and developed countries in Asia. The better ESG performance can reduce the company's firm financial distress risk from bankruptcy as indicated by the increasingly high Altman Z-Score. The conclusion of the study is that the ESG score is an important factor for companies in sustainable business development.